Effect of Astragalus fasciculifolius (Anzaroot) gel on episiotomy pain in primiparous women: A Triple Blind Randomized Controlled Trial - Arezoo Beiromvand; Afsaneh Yegdaneh; Safoura Rouholamin; Mahboubeh Valiani; niloofar Naghi Ganji; reza Biranvand (Mashhad University of Medical Sciences, 2020)
Introduction: Episiotomy is the most common incision in midwifery to increase the diameter of pelvic outlet. Anzaroot contain flavonoid, saponin, tryptophanes, tannins and other polyphenolic compounds. So it has analgesic properties. This study was performed with aim to determine the effect of Astragalus fasciculifolius (Anzaroot) gel on episiotomy pain severity in primiparous mothers. Methods:This three-blind clinical trial study was conducted on 72 primiparous women referred to Shahid beheshti hospital in Isfahan in 2019. They were randomly divided into two equal groups of experiment (Anzaroot) and control (Placebo gel). Severity of pain was assessed using the visual pain scale (VAS). Data were analyzed by SPSS software (version 16) and Independent Samples T Test, covariance analysis and repeated Measures analysis. P˂0.05 was considered statistically significant. Results: There was no significant difference between two groups in demographic features and obstetric variables (P˃0.05). Before the intervention, no significant difference was observed between two groups in the severity of pain (P=0.16(. After the intervention, severity of pain in the experiment group was significantly less than the control group (p < 0.05). Conclusion: Anzaroot gel is more effective than placebo in relieving of episiotomy pain.